Forecasting tourism demand for Lisbon´s region : a data mining approach - Ricardo, Hugo David dos Reis Barbosa (2018)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management